1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Definite integration, even function. confused about proof

  1. Apr 13, 2013 #1
    1. The problem statement, all variables and given/known data
    Let [itex]f[/itex] be integrable on the closed interval [itex][-a,a][/itex]

    If [itex]f[/itex] is an even function, then
    [itex]\int^a_{-a}f(x)\,dx[/itex] = [itex]2\int^a_0f(x)\,dx[/itex]

    Prove this.

    2. Relevant equations

    3. The attempt at a solution
    The solution is given in the book.

    Because [itex]f[/itex] is even, you know that [itex]f(x) = f(-x)[/itex]. Using the substitution [itex]u = -x[/itex] produces

    [itex]\int^0_{-a}f(x)\,dx =\int^0_af(-u)\,(-du) = -\int^0_af(u)\,du
    =\int^a_0f(u)\,du = \int^a_0f(x)\,dx[/itex]

    Now that part that confuses me is [itex]\int^a_0f(u)\,du = \int^a_0f(x)\,dx[/itex]

    Wouldnt [itex]u=-x[/itex] mean [itex]du=-dx[/itex] which would produce [itex]\int^a_0f(u)\,du = -\int^a_0f(x)\,dx[/itex]

    I know my reasoning must fall apart somewhere, since that would mean

    If [itex]f[/itex] is an even function, then [itex]\int^a_{-a}f(x)\,dx = 0[/itex].

    I just cannot see how my reasoning is wrong.

    If it makes any difference this is the remainder of the proof in the book.

    [itex]\int^a_{-a}f(x)\,dx =\int^0_{-a}f(x)\,dx + \int^a_0f(x)\,dx
    =\int^a_0f(x)\,dx + \int^a_0f(x)\,dx = 2\int^a_0f(x)\,dx[/itex]
  2. jcsd
  3. Apr 13, 2013 #2
    You can label the integration variable in a definite integral with any letter, it does not change anything. The definite integral is completely determined by the function under the integral sign and its limits. ## \int_a^b f(x)dx = \int_a^b f(u)du = \int_a^b f(\xi)d\xi = \int_a^b f(\mathfrak{S})d\mathfrak{S} ##
  4. Apr 13, 2013 #3
    No because switching [itex] u \leftrightarrow x [/itex] you also have to switch the limits of
    integration, which is what you did in the first place but don't do here!

    [itex]u=-x[/itex] mean [itex]du=-dx[/itex] which would produce [itex]\int^a_0f(u)\,du = -\int^{-a}_0 f(x)\,dx[/itex]
  5. Apr 14, 2013 #4
    Oh right. I see the mistake I made. Thanks qbert.

    But I still dont see how that leads to [itex]\int^0_{-a}f(x)\,dx = \int^a_0f(x)\,dx[/itex]

    I was looing at it as if the author was using a theorem he proved earlier in the text:

    If [itex]u=g(x)[/itex] has a continuous derivative on the closed interval [itex][a,b][/itex] and [itex]f[/itex] is continuous on the range of [itex]g[/itex], then

    [itex]\int^b_af(g(x))g'(x)\,dx = \int^{g(b)}_{g(a)}f(u)\,du[/itex]

    Im not completley sure but, it would seem the author did use it until he got to the point [itex]\int^a_0f(u)\,du = \int^a_0f(x)\,dx[/itex]

    Are you saying that when the author got to that point he didnt change the variable, but just relabled it?
  6. Apr 14, 2013 #5
    A real change of variables typically changes both the integrand and the limits. This is what the author had till the final step. Then, yes, he simply re-labeled the variable. How can you tell? It did not change the integrand, nor the limits.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted